Limits to fishing: the case for collective self-limitation illustrated with an example of small-scale fisheries in Catalonia - Nogué-Algueró, Borja; Kallis, Giorgos; Ortega, Miquel (Frontiers in Marine Science, 2023)
Is there a limit to the amount of fish that can be taken from the sea? This question echoes the concern of the broader environmental movement in asking: are there ‘limits to growth’? If the answer is ‘yes’, then what must be done to remain within sustainable limits? Fifty years after the publication of the landmark report Limits to Growth, new theories about limits highlight the importance of collective self-limitation, also in the context of fisheries management, in place of external, top-down determination and imposition of limits. This paper considers the shift in fisheries governance from regulating and establishing Maximum Sustainable Yields to collectively co-managing territories and ecosystems as symptomatic of a general turn from externally-imposed to self-imposed limitations. We show how perceptions and practices of limits are changing based on an ethnographic study of six small-scale fisheries co-management plans located off the Catalan coast in the Northwestern Mediterranean. The study evidences the challenges fishers face in attempting to define the limits of their agency to manage external forces that are often beyond their control. It concludes by arguing for the adoption of an ethos of collective self-limitation in fisheries governance to protect and benefit local communities and their environments.